From Colonial Aesthetics to Nationalist Visuals: Film Advertising Design in Indonesia, 1950s–1970s - Rachmad, Ageng; Triyanto, Jefri Rieski; Mutmaina, Rima Nur (Universitas Negeri Padang, 2025)
Film is a modern medium used to deliver entertainment that has previously been a tradition in society, including presenting elements such as narrative, events, music, drama, comedy and other elements to a wide audience. The novelty of this study lies in examining the visual shift in Indonesian film advertisements from colonial-influenced Western styles toward emerging nationalist aesthetics during the 1950s–1970s, a transformation that has not been previously explored in historical cinema research. The aim of this study is to provide a focused analysis of the visual representation and graphic design of Indonesian film advertisements from the 1950s–1970s using the theoretical perspectives of visual culture and advertising theory to clarify how typography, image composition, and stylistic choices in these promotional materials reflected the cultural context of the era. The method used in this research is the historical method according to Kuntowijoyo which starts from (1) topic selection, (2) heuristics, (3) criticism, (4) interpretation and (5) historiography. The results of this study provide a descriptive account of Indonesian cinema in the 1950s–1970s while showing how film advertisements in newspapers and magazines reflected the broader social and political transitions of the period, including the shift from colonial-influenced visual styles toward emerging nationalist expressions. Movie advertisements in the early 1950s still displayed strong colonial visual nuances, especially through Hollywood-style image composition that imitated the promotional aesthetics of Western imported films dominating Indonesian cinemas at the time. This visual tendency was closely related to the dominance of imported Western films in Indonesian cinemas at the time, which influenced the stylistic choices of local promotional designs. Although there were still few domestically made films, the advertisements had begun to insert symbols of resistance to western domination by incorporating local elements.